THE ANALYSIS OF THE THREE DIMENSIONAL MATERIAL OBSERVED FROM THE MATHEMATICAL CRITICAL THINKING ABILITY OF HIGH SCHOOL STUDENTS BY APPLYING BRAIN BASED LEARNING (BBL) - Repanda Sayoga; Putri Eka Indah Nuurjannah (IKIP Siliwangi, 2019)
The background of this research was that the mathematical critical thinking ability of the students is still low. Therefore, the purpose of this study was to find out the misconceptions or difficulties of students in each indicator of mathematical critical thinking ability of high school students that learned Brain Based Learning (BBL) with material in the Three Dimensions. This reseacrh used a qualitative approach with the descriptive method. The subjects in this study were the students of XII MIPA 5 class or first grade of senior high school in Subang Regency which was on a total of 32 students. The instrument of this study consisted of a test instrument of mathematical critical thinking ability and a non-test instrument in the form of an observation sheet. The results of this study shows that students almost have difficulty in carrying out tests of mathematical critical thinking skills based on the indicators tested. The indicators of critical thinking ability tested include providing simple clarification (elementary clarification), making conclusion (inference), determining strategies and tactics (strategies and tactics) to solve problems, and making further clarification (advances clarification).